A biographical narrative study of deans’ responses to corporatisation of higher education in Uganda: a case study of Makerere University - Mwebesa, Christine Charity (My University, 2020)
Globally, Higher Education (HE) has undergone transformation because of several factors. Some of these transformations are endorsed by international monitoring bodies, like the World Bank and International Monetary Fund (IMF). While such interventions aimed at improving effectiveness and efficiency of academic institutions, they were received with mixed reactions. One such transformation is the corporatisation of HE, which is conceptualised in this study as the adoption of managerial models and private sector practices into Higher Education Institutions (HEIs), with the intention of achieving self-sustainability and global competitiveness, while maintaining local relevance. While extant literature draws a dichotomy between opponents and proponents of corporatisation of HE, it falls short of offering justification for the lived experiences of Deans in a seemingly already corporatised environment. Thus, the study sought to answer one major question: How do deans at Makerere University respond to corporatisation of HE in their academic space? Three sub-questions used were: • What is the understanding of deans of the notion of corporatisation of HE at Makerere University? • How has the deans’ lived experiences of corporatisation of HE influenced their roles, values and careers within the university? • How can the deans’ lived experiences inform policy of managing university reforms at Makerere University? A qualitative research approach, springing from an interpretive paradigm, and a narrative research design were used. Data was collected from university policy documents and a modified Biographical Narrative Interpretive Method (BNIM) interviewing technique. Fourteen (14) deans were purposively selected and seventeen (17) interviews generated (basing on BNIM three step interviews). Data from the interviews was transcribed and analysed both descriptively and interpretively, following Kelchtermans’ two phased process (1993). Two change theories and a model of organisational cultural framework were integrated to make sense of the data: Schein’s model (deans’ conceptualisation of corporatisation), selfdetermination theory (influence of corporatisation on deans’ values, careers and roles) and the competing values framework (beyond the divergence of corporate and academic values/models). Three constructs emerged from the analysis of data: passion, position and purpose, all of which, together with the traffic lights’ metaphor, were instrumental in identifying the three major categories (Rejectors, Embracers and Integrators) and five sub-categories (Challengers, Contemplators, Complimentors, Co-Implementors and Consolidators) of deans that emerged in the study. The study showed that deans’ responses unveiled their purpose (save, serve or solve) and position (as irredeemable, improvable or implementable) in support of, or against the entry of corporatisation. The manner in which the reform was received and implemented was influenced by the stand deans took. Also, the critical multifaceted role of deans in the university functions was revealed through the five broad themes identified: Quality, Governance, Access, Finances and Stakeholders, with 10 subthemes (quality as a product, quality as a process, role of government, role of university management, integrative role of deans, entry access, epistemic access, exit access, source of funding, comptroller of funds, stakeholder relationships and stakeholder management). Finally, the deans’ mediation role was brought to the fore in harmonising all the university’s stakeholder relationships (both external and internal). Lastly, it was evident that, to harness and effectively manage any university reforms or interventions, deans must take centre stage. The study, therefore, proposes a model beyond the competing values to an Integrative Complementing Model for HE reforms (ICM4HEr), which recognises and recommends deans’ mediating role for a productive relationship with all university stakeholders. For equitable access, the study recommends scrapping of government sponsorship at Makerere University, using the money to equip regional universities and support a regional quota for students from poor backgrounds. It further recommends more studies that compare deans’ experiences regarding corporatisation in private and public universities, as well as a similar study that looks at all categories of university staff, students and different levels of leadership using mixed methods.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020
Keywords: Education, Higher--Uganda; Academic freedom--Political aspects--Uganda; Educational change